Analysis of Discounts in Shopeepay Transactions: Perspective of Islamic Law and Sociology of Law - Salma Nurul Fadhilah; Arinto Nurcahyono (IAI Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2024)
The development of digital technology has driven changes in economic transactions, including the increasing use of digital wallets such as shopeepay. Shopeepay offers ease of transactions as well as various promos such as discounts and cashback that attract consumers. However, from the perspective of Islamic law, there is a debate about the validity of this transaction, especially related to the element of riba in the profits obtained by users. In addition, from the perspective of legal sociology, the use of shopeepay reflects how society navigates Islamic legal norms in modern economic practices. This research uses a descriptive qualitative method with a legal sociology approach. Data is collected through literature studies by analyzing relevant literature, including journals, books, and articles. The analysis was carried out by identifying people’s behavior patterns in the use of shopeepay as well as the influence of social norms and economic interests on compliance with Islamic law. Promos and incentives provided by shopeepay can be categorized as riba nasi’ah because they come from funds saved by users. Despite this, many people continue to use shopeepay because of its economic benefits, showing that economic interests are often more dominant than compliance with Islamic law. Therefore, stricter supervision from regulators and public education regarding digital transactions in accordance with sharia principles is needed.